2017
DOI: 10.1186/s13049-017-0446-1
|View full text |Cite
|
Sign up to set email alerts
|

EMT-led laryngeal tube vs. face-mask ventilation during cardiopulmonary resuscitation - a multicenter prospective randomized trial

Abstract: BackgroundLaryngeal tube (LT) application by rescue personnel as an alternate airway during the early stages of out-of-hospital cardiac arrest (OHCA) is still subject of debate. We evaluated ease of handling and efficacy of ventilation administered by emergency medical technicians (EMTs) using LT and bag-valve-mask (BVM) during cardiopulmonary resuscitation of patients with OHCA.MethodsAn open prospective randomized multicenter study was conducted at six emergency medical services centers over 18 months. Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 21 publications
1
16
0
1
Order By: Relevance
“…In addition, Fiala et al found no difference between BMV and the LT for ventilating OHCA patients in a multicenter randomized study of EMT-led airway management. 14,15 Considering other EGDs, our findings are also consistent with multiple prior studies of inexperienced providers using laryngeal mask airways (LMA), all of which concluded that inexperienced airway providers (including nurses, nursing students, dental students, and other volunteers with no prior experience) can provide better ventilation with the LMA than with BMV (with or without a concomitant oropharyngeal airway). 5,[22][23][24][25][26] One study looking specifically at obese patients found that medical students were able to establish effective ventilation more quickly with the LMA than with BMV.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, Fiala et al found no difference between BMV and the LT for ventilating OHCA patients in a multicenter randomized study of EMT-led airway management. 14,15 Considering other EGDs, our findings are also consistent with multiple prior studies of inexperienced providers using laryngeal mask airways (LMA), all of which concluded that inexperienced airway providers (including nurses, nursing students, dental students, and other volunteers with no prior experience) can provide better ventilation with the LMA than with BMV (with or without a concomitant oropharyngeal airway). 5,[22][23][24][25][26] One study looking specifically at obese patients found that medical students were able to establish effective ventilation more quickly with the LMA than with BMV.…”
Section: Discussionsupporting
confidence: 89%
“…Studies examining minute ventilation as well as those using a subjective outcome of "adequate ventilation" as judged by the care provider have yielded conflicting results when examining the efficacy of LT versus BMV. 3,8,14,15 We therefore aimed to compare ventilation efficacy of inexperienced airway providers with BMV versus LT on a simulated model. Our primary outcome was measured tidal volume, and our secondary outcome was peak pressure.…”
Section: Introductionmentioning
confidence: 99%
“…To improve OHCA outcomes, many countries are applying various strategies to their emergency medical services (EMS) 123. Previous reports of prehospital EMS interventions, including dispatch type, airway management, and the number of emergency medical technicians (EMTs) have been reported 4567891011. Among these, multi-dispatch response to an OHCA, using more than two EMS teams of the same or different tiers, have shown some positive effects 67111213.…”
Section: Introductionmentioning
confidence: 99%
“…Effective ventilation is an important component in survival and is associated with return of spontaneous circulation (ROSC) and neurological recovery (1). However, the most optimal method for effective ventilation is still under debate (2).…”
Section: Introductionmentioning
confidence: 99%